Livestock Depredation by Tiger in and around Dudhwa National Park, Uttar Pradesh and Mitigation Strategies - Chauhan, N. P. S. (Indian Forester, 2005)
The Dudhwa National Park has had a long-standing problem of cattle lifting by tigers. The available tiger habitats are embedded in a matrix of human altered landscape, the humantiger interface is of serious concern, especially in the context of livestock depredation. This has led to a strong resentment among people who show increased apathy and antagonism towards tiger conservation. The paper focuses on the pattern of livestock depredation in and around the Dudhwa National Park and suggests mitigation strategies.